Pengaruh current ratio, return on asset, dan return on equity terhadap harga saham - Icha Sandrina, Icha Sandrina; Suryaningprang, Andre; Sudaryo, Yoyo; Herlinawati, Erna; Saputro, Arie Hendra (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
The purpose of this study was to examine the effect of inventory costs at PT HM Sampoerna Tbk on the Current Ratio (CR), Return On Assets (ROA), and Return On Equity (ROE). This research uses descriptive, quantitative, and verification methods based on empirical philosophy. For this reason, this study uses a purposive trial examination which produces one organization from 2012-2021. This study used the documentation strategy and information selection in the quantitative methodology. The organization's official website, the Indonesia Stock Exchange (IDX), and other supporting pages provide information. Microsoft Succeed, and SPSS 25 were used to carry out examinations in this study. Based on the findings of this study, inventory costs are jointly influenced by Current Ratio (CR), Return On Assets (ROA), and Return On Equity (ROE).